Kontribusi Konformitas terhadap Pencapaian Identitas Diri Remaja di Desa Bandar Tinggi Kabupaten Labuhan Batu - Rambe, Nur Arapah; Santosa, Budi (YASIN, 2023)
The large number of adolescents conforms to their peers, so that they can be accepted by the environment, this affects adolescent self-identity considering that adolescence is a period of searching for identity. The aim of the research is to see how much conformity contributes to the achievement of adolescent self-identity in Bandar Tinggi Village, Labuhan Batu Regency. Quantitative research method with regression data analysis techniques. The research population was early adolescents, as many as 10 people, 10 middle adolescents, and 10 late adolescents. The sample in this study were 30 people. In taking samples, the authors use total sampling technique. Data was collected using a questionnaire instrument with a Likert scale type. Data analysis techniques used the normality test, linearity test, and hypothesis testing using a determination test, simple linear regression test and the F test (Simultaneous) with the help of SPSS version 20. The results of the study showed that the Fcount value was 10.598 with a sig value of 0.003. This shows that the Fcount value is greater than Ftable (10.598> 4.20) and the sig value is less than 0.003. Thus H_0 is rejected and H_1 is accepted, meaning that conformity has a significant effect on achieving self-identity. These results indicate that there is a significant effect of conformity on adolescent self-identity in Bandar Tinggi Village, Labuhan Batu Regency. Furthermore, the determination index is 27.5%, meaning that conformity has an influence on self-identity in Bandar Tinggi Village, Labuhan Batu Regency by 27.5% and 72.5% % influenced by other factors.